Studi Endapan Paleotsunami di Desa Hila, Kecamatan Leihitu, Kabupaten Maluku Tengah, Provinsi Maluku - Anisha Marizka Angkotasan; Zulfiah; Aswan (Mataram University, 2026)
Hila Village, located in Leihitu District, has a historical record of a major tsunami event in 1674; however, the geological evidence of this event has not been comprehensively studied. This research aims to identify and characterize paleotsunami deposits in Hila Village and to distinguish them from modern beach deposits and other coastal sediments. The study employed field observations, megascopic fragment analysis, granulometric analysis, and laboratory identification of foraminiferal microfauna. The results indicate that the paleotsunami deposits are characterized by poorly sorted sediments with grain sizes ranging from fine sand to gravel and cobble, erosional basal contacts, mixed lithic fragments, and benthic foraminifera derived from inner to outer neritic environments. Fragment analysis shows dominance of disc and blade morphologies, low sphericity, angular to sub-rounded roundness, and floating clasts within a sandy matrix. The deposits consist of mixed materials, including igneous rock fragments, coral debris, and anthropogenic materials, reflecting rapid high-energy transport and sediment mixing from multiple source environments. These characteristics clearly differ from modern beach deposits, which are generally better sorted, clast-supported, and influenced by repetitive wave abrasion processes.